Comparing differences and relationships between traditional and resisted sprints in elite youth rugby backs and forwards - Zabaloy, S.; Freitas, T. T.; Tomaghelli, L.; Aparicio, J.; Vega, F.; Medrano, J.; Tondelli, E.; Pereira, L. A.; Loturco, I. (International Journal of Sports Physiology and Performance, 2025)
Purpose We tested the differences in maximum strength and various parameters of sprint performance between youth backs and forwards. Additionally, we examined the associations among various strength-sprint measures, as well as between unresisted and heavy resisted sprints.